2005
DOI: 10.1016/j.bbmt.2004.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Onset of thymic recovery and plateau of thymic output are differentially regulated after stem cell transplantation in children

Abstract: Thymus-dependent T-cell regeneration is a major pathway for immune reconstitution after stem cell transplantation in children. Therefore, we prospectively assessed T-cell dynamics and thymic function in 164 pediatric patients between 1 and 124 months after transplantation by measuring T-cell receptor recombination excision circles and spontaneous expression of Ki67 in peripheral T-cell subsets. We analyzed the effect of recipient age, conditioning regimen, type of donor and graft, stem cell dose, and graft-ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 39 publications
5
33
0
2
Order By: Relevance
“…As previously reported, 29 the initiation of regeneration of naive T lymphocytes and thymic function appeared by 6 months post transplant among the allogeneic recipients. 26,29 The recovery of the naive CD4 þ T lymphocytes post HSCT has been shown to be protracted also in children. 30,31 In previous studies, data on immune reconstitution has been compared with either healthy, age-matched controls 31 or within subgroups.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…As previously reported, 29 the initiation of regeneration of naive T lymphocytes and thymic function appeared by 6 months post transplant among the allogeneic recipients. 26,29 The recovery of the naive CD4 þ T lymphocytes post HSCT has been shown to be protracted also in children. 30,31 In previous studies, data on immune reconstitution has been compared with either healthy, age-matched controls 31 or within subgroups.…”
Section: Discussionsupporting
confidence: 54%
“…32,33 Also in our study, aGVHD did not affect the regeneration of the naive T cells or TRECs post HSCT. However, and as previously reported, [14][15][16]29 low TREC levels did associate with extensive cGVHD post HSCT. Patients with cGVHD have a reduced capacity to produce naive CD4 þ T cells 34 because of thymic epithelial injury by GVHD and immunosuppressive drugs.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A negative correlation between increasing age and numbers of naïve CD4 þ T cells and TRECs after autologous and allogeneic SCT or chemotherapy has been reported in a variety of studies. [75][76][77][78][79] Some studies in MAC-SCT setting have shown age as the main determinant of T-cell reconstitution after SCT. Eyrich et al 79 analyzed in a series of 164 pediatric recipients of allogeneic myeloablative transplantation (median age 7.5 years, range 0.3-22.6 years) the effect of recipient age, conditioning regimen, type of donor and graft, stem cell dose and GvHD on the onset and the plateau of thymic output after transplantation.…”
Section: Patient's Agementioning
confidence: 99%
“…This suggests homeostatic proliferation as the substantial mechanism of T-cell repopulation in early phases after treatment, as described during lymphopenia. 35 Other investigators have proposed that the rapid proliferation observed after BMT is mainly associated with the occurrence of GVDH and infection. 36 In this regard, it is important to note that most GT patients did not experience infectious complications, and the GVHD-related bias is unlikely to occur because of the autologous nature of the transplant.…”
Section: Discussionmentioning
confidence: 99%